Application of Modulo and Zeller Concepts in Determining the Beginning of Ramadan and the Beginning of Shawwal in 1443 H-1447 H - Juliansyah, Muhammad Farhan; Sajidah, Hanah Dewi; Wahdani, Lutfi; Ramadhani, Muji Indah Rahayu; Surur, Agus Miftakus (University of Muhammadiyah Sumatera Utara, 2024)
This study aims to calculate the estimate of when the beginning of the month of Ramadan and the month of Shawwal. In addition, it is also used to find out whether there are differences and similarities when determining the beginning of the month of Ramadan and the month of Shawwal using the mathematical concept of modulo 7 and Zeller's congruence. This research is a qualitative research with a literature study approach to investigate scientific literature related to the concept of modulo and Islamic calendar calculation methods. This research focuses on the concept of modulo in determining the beginning of Ramadan and Shawwal. The results of this study indicate that using the calculation of Zeller's congruence is more precise or closer than using the calculation of the modulo 7 concept seen from the 1443 H-1447 H calendar. This research provides an important contribution in understanding the calculation of the Islamic calendar, especially in determining the beginning of Ramadan and Shawwal with the mathematical concepts used such as modulo